Singular Boundary Method to Simulate Scattering of SH Wave by the Canyon Topography (Advances in Applied Mathematics and Mechanics, 2018)
This study presents an alternative meshless boundary collocation approach,the singular boundary method (SBM), in conjunction with the image concept for simulatingSH wave scattering by the canyon topography. First the image concept is implementedto extend the original semi-infinite domain problems to infinite domain problems.Then the SBM has been used to solve the infinite domain problems. In the SBMit employs the singular fundamental solutions as basis functions and introduces theconcept of source intensity factor to regularize the singularities of the related fundamentalsolutions, which avoids singular numerical integrals in the boundary elementmethod. To demonstrate the effectiveness of the proposed approach for SH wave scatteringby the canyon topography, several benchmark examples are considered. Thepresent results are compared with the analytical solutions, the null-field boundary integralequation method.